Crystal structure of bis(benzyltriethylammonium) hexachlorotellurate(IV), [C7H7(C2H5)3N]2(TeCl6) - Caracelli, I. [UNESP] (De Gruyter, 2004)
C26H44Cl6N2Te, monoclinic, P121/n1 (no. 14), a = 9.3981(5) Å,b= 14.606(1) Å, c = 12.4524(7) Å, β = 108.335(5)°, V= 1622.6 Å3, Z = 2, Rgt(F) = 0.024, wRref(F2) = 0.065, T= 293 K. © 2014 Oldenbourg Wissenschaftsverlag GmbH, Rosenheimer Str. 145, 81671 München. All rights reserved.